A dual-plane fluoroscope to track joint kinematics during dynamic daily activities - Albert Planta; Raphael Surbeck; William R. Taylor; Stefan Plüss; Florian Vogl; Pascal Schütz (PLoS ONE, 2025)
Accurate measurement of joint kinematics is a key requirement for understanding injury mechanisms, evaluate rehabilitation techniques, and improve the implant designs and techniques used in total knee arthroplasty (TKA). Fluoroscopy is an experimental technique to directly measure joint kinematics without being affected by soft-tissue artefacts. However, because of its limited field-of-view (FOV), stationary fluoroscopy can only measure small parts of more dynamic/progressive movements, such as walking. This manuscript presents a new generation of moving fluoroscope: The tracking dual-plane fluoroscope (tDPF) combines optical tracking with a bi-planar X-ray system on mechanically independent source and intensifier carriages on rails and model-predictive-control to measure the kinematics of the tibio-femoral joint in vivo during dynamic activities, such as level walking and stair ascent/descent, at all gait speeds. In this proof-of-concept study, the tDPF tracked the knees of 16 young and healthy subjects during complete, consecutive gait cycles of level walking, ramp ascent, ramp descent, stair ascent, and stair descent at self-selected gait speeds. For all gait speeds (average and standard deviation: 1.34±0.14m s−1 during level walking), tracking performance for each activity was excellent and the knee centre stayed within both simulated image intensifiers’ FOVs for >99% of frames (no X-ray images were captured in this study). The tDPF is the first dual-plane fluoroscope to track the knee joint during entire cycles of stair and ramp ascent at self-selected gait speeds for young and healthy subjects. Notably, our device does not require any pre-recording of movement patterns—by using real-time position estimates of the tracked joint and tracking each trial independently, even the challenging measurements of tasks with high variability between trials become possible.